ECONOMIC MECHANISMS OF ENSURING THE NATIONAL INTERESTS OF A MODERN STATE - Olga Mikhailovna Litvishko (Современная наука и инновации)
The characteristic feature of modern international relations is the growing influence of economic factors on foreign policy. Under the conditions of economization of international relations states need to develop new strategies which will be adequate for the demands of the globalized world community.